The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.5194/amt-11-925-2018
|View full text |Cite
|
Sign up to set email alerts
|

Collocation mismatch uncertainties in satellite aerosol retrieval validation

Abstract: Abstract. Satellite-based aerosol products are routinely validated against ground-based reference data, usually obtained from sun photometer networks such as AERONET (AEROsol RObotic NETwork). In a typical validation exercise a spatial sample of the instantaneous satellite data is compared against a temporal sample of the point-like ground-based data. The observations do not correspond to exactly the same column of the atmosphere at the same time, and the representativeness of the reference data depends on the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 32 publications
(50 reference statements)
2
29
1
Order By: Relevance
“…Station data, whether AERONET or MAN, is allocated to whichever grid-box they fall in. Point observations will always suffer from representativeness issues (Sayer et al, 2010;Virtanen et al, 2018;Schutgens et al, 2016a), but the representativity of AERONET sites for 1 o × 1 o grid-boxes is fairly well understood (Schutgens, 2019), see also Section 4.…”
Section: Collocation and Analysis Methodologymentioning
confidence: 99%
“…Station data, whether AERONET or MAN, is allocated to whichever grid-box they fall in. Point observations will always suffer from representativeness issues (Sayer et al, 2010;Virtanen et al, 2018;Schutgens et al, 2016a), but the representativity of AERONET sites for 1 o × 1 o grid-boxes is fairly well understood (Schutgens, 2019), see also Section 4.…”
Section: Collocation and Analysis Methodologymentioning
confidence: 99%
“…However, the spread among the products is slightly more pronounced in summer ( Fig. A1 for JJA, summer for the Northern Hemisphere), when the absolute AOD often reaches its maximum in certain regions (e.g., in China, Sogacheva et al, 2018).…”
Section: Aod Spatial Distributionmentioning
confidence: 99%
“…Similarly, Li et al (2009) concluded that differences in cloud-masking alone could account for most differences among multiple satellite AOD datasets, including several for which different algorithms were applied to data from the same instrument. Due to these discrepancies, none of the satellite AOD products gives identical values of aerosol properties or is uniformly most accurate (de Leeuw et al, 2015(de Leeuw et al, , 2018Kinne et al, 2006). In other words, there is no single "best" AOD satellite dataset globally.…”
Section: Introductionmentioning
confidence: 99%
“…In brief, this method uses spatial averaging of satellite data and temporal averaging of AERONET data to account for the fact that AERONET provides point measurements of AOD with a sampling frequency of 5–15 min (dependent on instrument configuration) in cloud‐free conditions, while satellites provide an instantaneous swath measurement with individual retrieval footprints covering several to tens of kilometers. This fundamental difference introduces some uncertainty beyond that of AERONET alone, dependent on the level of heterogeneity in the underlying aerosol field (Virtanen et al, ). Since the publication of prior SOAR validation papers (Sayer, Hsu, et al, ; Sayer, Hsu, Bettenhausen, et al, ; Sayer, Hsu, Lee, et al, ), updates have been made to both the AERONET data version and the specifics of the validation methodology, and as a result these are described in full below.…”
Section: Validation Against Aeronetmentioning
confidence: 99%
“…In particular, for example, as noted earlier the bulk of the dust aerosol model matchups is for sites sampling Saharan outflow so error characteristics for other dust‐laden regions may differ (i.e., these metrics may not capture regional variations within a given type). A second limitation is that it folds in some of the uncertainties related to the matchup method and AERONET data rather than the retrieval itself (e.g., Virtanen et al, ). Practically speaking, it would also be reasonable to assume a minimum possible uncertainty of ∼0.01 on the basis of the radiometric uncertainty in the TOA reflectance measurements.…”
Section: Validation Against Aeronetmentioning
confidence: 99%